2014
DOI: 10.4161/cc.28112
|View full text |Cite
|
Sign up to set email alerts
|

Environmental signaling through the mechanistic target of rapamycin complex 1

Abstract: Mechanistic target of rapamycin complex 1 (mTORC1) is a well-known regulator of cell growth and proliferation in response to environmental stimuli and stressors. To date, the majority of mTORC1 studies have focused on its function as a cytoplasmic effector of translation regulation. However, recent studies have identified additional, nuclear-specific roles for mTORC1 signaling related to transcription of the ribosomal DNA (rDNA) and ribosomal protein (RP) genes, mitotic cell cycle control, and the regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 156 publications
(237 reference statements)
1
22
0
Order By: Relevance
“…In addition, the functional relevance of the nuclear mTORC1 has also been indicated (Workman et al, 2014). However, it is unclear whether functional endogenous mTORC1 exists in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the functional relevance of the nuclear mTORC1 has also been indicated (Workman et al, 2014). However, it is unclear whether functional endogenous mTORC1 exists in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been suggested that there is little intact mTORC1 in the nucleus due to low affinity of nuclear raptor to mTOR than cytoplasmic raptor (Rosner and Hengstschlager, 2008). On the other hand, nuclear mTORC1 signaling has been suggested to play a role in some cellular processes, including promoting the transcription of metabolic genes for ribosome biogenesis, lipid formation, and mitochondrial function (Back and Kim, 2011; Workman et al, 2014). For instance, it has been shown that mTOR binds to TFIIIC, a transcription factor that binds to pol III promoters, leading to enhanced protein synthesis in response to nutrients and growth factors (Kantidakis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…TORC1 is closely associated with the vacuolar membrane in many different organisms, whereas TORC2 is associated with the plasma membrane (39 -42). More recently, many studies have shown that TORC1 (39,(41)(42)(43)(44)(45) and TORC2 (39 -42) are also found in the nucleus and are required for several nuclear functions. AKT, the kinase acting downstream of mTORC2, was also originally located to the plasma membrane but is currently known to have additional functions in the nucleus (28,32,34,36,46).…”
Section: Torc2-gad8 Is Found In the Nucleus And Ismentioning
confidence: 99%
“…To date, a majority of studies have focused on the roles of the TORC signaling pathway as a translational regulator with its location in the cytoplasm (Workman et al 2014). Consequently, the role of mTOR in oncogenesis is thought to be largely due to its activity in the cytoplasm and increased translation of protumorigenic genes (Back & Kim 2011).…”
Section: Functional Connection Between Tor and Mitochondriamentioning
confidence: 99%